Coercive Authority and Trust in Tax Authority in Influencing Voluntary Tax Compliance: A Study of Slippery Slope - Uswatun Khasanah; Sutrisno T.; Endang Mardiati (Journal of Accounting and Investment, 2019)
The improvement of tax compliance in Indonesia has not resulted in increase of tax ratio of the same year. From this perspective, the researchers conducted a study on voluntary tax compliance using theory of slippery slope. This study aims to provide an empirical evidence on the potential influence of tax audits, tax rewards, and trust in tax authority towards voluntary tax compliance. The study was conducted on Corporate Taxpayers who were registered as PKP (Taxable Enterprise). Structural Equation Modeling-Partial Least Square (SEM-PLS) was employed as the analytical tool in the study. Our empirical findings show that tax audits could influence voluntary tax compliance and trust in tax authority was proven successful to reduce the influence of tax audit towards voluntary tax compliance. However, other findings also show that rewards were not proven successful in influencing voluntary tax compliance.